2022
DOI: 10.3389/fimmu.2021.825226
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Variety of Target Antigens During 1 Year Follow-Up of a Patient Initially Diagnosed With Bullous Pemphigoid

Abstract: Autoimmune bullous diseases (AIBDs), presenting cutaneous and/or mucosal bullous lesions, are classified into pemphigus and pemphigoid diseases. A longtime observation for complicated AIBD cases is rarely reported. In this study, serum samples of one AIBD patient were collected at seven different time points during the disease course including a relapse, which were examined by our conventional and newly developed methods for the detection of autoantibodies. Interestingly, we found changes of both the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This case showed very complicated immunological profile of IgG and IgA autoantibodies to multiple autoantigens during the disease course, although this case might be simply diagnosed as bullous pemphigoid or anti-BP180-type MMP, if the comprehensive autoantibody screening was not performed. The results in this study emphasized the importance of comprehensive autoantibody screening with different immunoglobulin types for multiple time points ( 4 , 10 ).…”
Section: Discussionmentioning
confidence: 65%
“…This case showed very complicated immunological profile of IgG and IgA autoantibodies to multiple autoantigens during the disease course, although this case might be simply diagnosed as bullous pemphigoid or anti-BP180-type MMP, if the comprehensive autoantibody screening was not performed. The results in this study emphasized the importance of comprehensive autoantibody screening with different immunoglobulin types for multiple time points ( 4 , 10 ).…”
Section: Discussionmentioning
confidence: 65%
“…With the disease progression, one subtype of AIBDs might shift to another subtype, or concur with other subtype(s) of AIBDs [ 75 , 76 ]. Therefore, during therapy, it is necessary to repeatedly test autoantibodies and autoantigens, which may suggest a change of treatment regimens.…”
Section: Endingmentioning
confidence: 99%
“…Recently, we reported one patient with complicated autoimmune bullous diseases (AIBD), which occurred as bullous pemphigoid and reoccurred as bullous pemphigoid combined with mucosal‐dominant‐type pemphigus vulgaris 1 . Serum samples were collected from this patient for autoantibodies analyses at seven different time points including days 0, 7, 55, 105, 120, 270, and 279 after admission 1 .…”
Section: Figurementioning
confidence: 99%
“…Recently, we reported one patient with complicated autoimmune bullous diseases (AIBD), which occurred as bullous pemphigoid and reoccurred as bullous pemphigoid combined with mucosal‐dominant‐type pemphigus vulgaris 1 . Serum samples were collected from this patient for autoantibodies analyses at seven different time points including days 0, 7, 55, 105, 120, 270, and 279 after admission 1 . Finally, we found that the changes in titers of autoantibodies against BP230 recombinant protein (RP), BP180 NC16a RP, and desmoglein (Dsg) 1 LQ144 peptide (intracellular domain) were well matched with the changes in clinical features during the whole disease course including a relapse on day 270 1 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation